The role of the priesthood in the process of nationalizing the church and school in Bessarabia after 1918 (Confluenţe Bibliologice, 2021)
In this article the author analyzes the partnership between the Church and the School, two great powers of the Nation that develop the mood and intellectual state in society. It presents the priesthood from Bessarabia, Bukovina, Transylvania and Old Romania who did their duty in drastic conditions during the Russian rule. It was the priesthood between the Prut and the Dniester, who accelerated the way of the political Union, but also of the spiritual one, of Bessarabia with the Motherland. So the author refers to the moments in which the cultural-moral values of a Nation are preserved and promoted, to the attitude of the Bessarabian Clergy together with the teachers in education, who contributed to maintaining the awareness of the Romanian national identity of the Bessarabian Modovans.
Keywords: union of Bessarabia with Romania; the history of the Romanians; priesthood